China's Expanding African Relations Implications for U.S. National Security - Thrall, Lloyd (RAND Corporation, 2015)
Across economic, political, and security domains, the growth of China's presence in Africa has been swift and staggering, which has fed both simplistic caricatures of China's role on the continent and fears of renewed geopolitical competition. A closer look reveals a more balanced picture. This report examines how China's growing engagement affects the United States' role in Africa and offers policy recommendations for U.S. military leaders.